Bioindicadores de qualidade do solo em sistemas integrados de produção agropecuária - Franco, Aline de Jesus (2019)
The growing food production has driven the expansion of agricultural areas in the country, especially in the Cerrado biome, with the use of different types of existing soil. But for this, it became necessary to adopt viable alternatives to improve production systems, management techniques such as Integrated Agricultural Production Systems (SIPA), no-tillage, crop rotation, intercropping and plant diversity. The adopted management reflects in the soil through the behavior of its chemical, physical and biological parameters, and commonly studies of these have been performed to verify its quality. Therefore, this research is to evaluate the interference of plant diversity and animal intake in SIPA and its effect on soil biochemical parameters in aOxisols(Latossolo Vermelhodistrófico) and a Entisols(Neossolo Quartzarênico). The study consisted of the evaluation of two experiments installed in the state of MatoGrosso. One of the experiments was carried out at FazendaGirassol, located in the municipality of PedraPreta, the soil of the area is classified as Oxisols(Latossolo Vermelhodistrófico). The randomized block design with three replications consisted of: D0 - Urochloabrizantha cv. BRS Paiaguás single cultivation; D1 - Paiaguás and cowpea (Vigna unguiculata); D2 - Paiaguás, cowpea and niger (Guizotia abyssinica); D3 - Paiaguás, cowpea, niger, buckwheat (Fogopyrum esculentum) and forage turnip (Raphanus sativus); SP - Paiaguás single cultivation without animals. The other experiment was carried out at the MatoGrosso Cotton Institute (IMA), in the city of Rondonópolis, and the soil was aEntisols(Neossolo Quartzarênico). The design was in randomized blocks with three replications. The treatments consisted of: S1 - Fallow; S2 - Urochloaruziziensis, niger and forage turnip; S3 - U. ruziziensis, niger, forage turnip and styling; S4 - U. ruziziensis and castor bean; S5 - U. ruziziensis, niger, forage turnip, styling and animals.In both experiments the biochemical parameters evaluated were: microbial biomass carbon (CMB), soil basal respiration (RBS), enzymatic activity (acid phosphatase, fluorescein diacetate hydrolysis, urease and β-glycosidase) and total glomalin. At the Sunflower Farm the CBM (233.63 - 333.39 μg g-1) and glomalin did not differ between treatments by Tukey test 5% after SIPA implantation. The enzymes acid phosphatase, β-glycosidase and urease were the most sensitive parameters in differentiating the adopted managements. In the IMA experiment, CBM values differed by the Tukey test at 5%, with values from 86 to 190 μg g-1, with the highest in treatments S3 and S5, which are the areas with the highest plant diversity. The enzymatic activity of the soil was sensitive to verify the differences between the adopted managements, where β-glucosidase ranged from 389 to 642 μg ρ-n g-1 and urease from 1.6 to 5.5 μg NH4-N g-1 h-1. The biochemical parameters were sensitive in indicating the best Integrated Agricultural Production Systems (SIPA) even in the short period of implementation.